ANALISIS PROGRAM BIMBINGAN BELAJAR UNTUK SISWA BERKESULITAN BELAJAR MEMBACA DI MI ISLAMIYAH GENUKWATU NGORO JOMBANG - Evita Widiyati; Nur Mufarokhatul Lathifah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2021)
This article discusses the tutoring program for students with learning difficulties in reading grade I at MI Islamiyah Genukwatu Ngoro Jombang. There are two focuses in this research, namely; 1) The process of implementing the tutoring program for students with learning difficulties in reading at MI Islamiyah Genukwatu Ngoro Jombang, and 2) The results of the tutoring program for students with learning difficulties in learning to read at MI Islamiyah Genukwatu Ngoro Jombang. By using a qualitative research approach, the type of research is a case study. In this case, the researcher tried to dig up the data by using observation, interview and documentation techniques. The data analysis technique uses data reduction, data presentation, conclusion drawing and verification. The technique of checking the validity of the data uses extension of participation, increasing the persistence of observations, triangulation of methods, and using reference materials. The results of the research on the Analysis of Tutoring Programs for Students with Learning Difficulties in Reading (Case Study at MI Islamiyah Genukwatu Ngoro Jombang), are; 1) The tutoring program is held every Tuesday and Thursday, starting at 07.30-08.30. Before the teacher starts the tutoring activity, the teacher invites to pray first. After that, the teacher asked the students to recall any letters of the alphabet, both vowels and consonants. Then the teacher explains the material about patent letters (an, in, en, on, and un). During the special tutoring process for students who have difficulty in reading, most of them are very enthusiastic in following it. It is proven by their attitude from the beginning to the end of the tutoring activity, and 2) The results after participating in the tutoring program, it is stated that the students have been able to overcome the problems of reading difficulties faced by each student. For example, being able to recognize letters, being able to memorize the names of letters, already recognizing letters and fluent in reading, being able to spell double letters, and being able to distinguish the letters b-d, u-n, m-n, p-q. So that each student is able to catch up with his friends who are already fluent in reading.